The Influence of Study Discipline, Reward Giving, Parental Support, and Learning Facilities on Phase F Learning Achievement Thru Student Learning Interest as an Intervening Variable in Economics Subjects - Khodija; Fifi Yasmi; Rika Verawati (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine: (1) the effect of learning discipline on academic achievement, (2) the effect of learning discipline on academic achievement through learning interest as an intervening variable, (3) the effect of reward on academic achievement, (4) the effect of reward on academic achievement through learning interest as an intervening variable, (5) the effect of parental support on academic achievement, (6) the effect of parental support on academic achievement through learning interest as an intervening variable, (7) the effect of learning facilities on academic achievement, (8) the effect of learning facilities on academic achievement through learning interest as an intervening variable, and (9) the effect of learning interest on academic achievement. This research is an associative study. The population in this study consisted of students from classes F3, F4, F5, and F6, with a total sample of 89 students selected using proportional random sampling. The research instrument used was a closed questionnaire, and the data analysis employed path analysis and t-test. The results of the study show that: (1) learning discipline has a positive and significant effect on learning interest with a path coefficient of 0.488 and a t-value of 5.536 > t-table 1.663, (2) reward has a negative and significant effect on learning interest with a path coefficient of -0.236 and a t-value of -2.946 > t-table 1.663, (3) parental support has a negative and significant effect on learning interest with a path coefficient of -0.168 and a t-value of -2.101 > t-table 1.663, (4) learning facilities have a positive and significant effect on learning interest with a path coefficient of 0.592 and a t-value of 7.132 > t-table 1.663, (5) learning discipline has a negative and significant effect on students’ academic achievement with a path coefficient of -0.284 and a t-value of -2.371 > t-table 1.663, (6) reward has a negative and significant effect on students’ academic achievement with a path coefficient of -0.244 and a t-value of -2.391 > t-table 1.663, (7) parental support has a positive and significant effect on students’ academic achievement with a path coefficient of 0.404 and a t-value of 3.884 > t-table 1.663, (8) learning facilities have a negative and significant effect on students’ academic achievement with a path coefficient of -0.269 and a t-value of -2.019 > t-table 1.633, and (9) learning interest has a positive and significant effect on students’ academic achievement with a path coefficient of 0.536 and a t-value of 3.879 > t-table 1.975.